Essential communications skills for managers. Volume II, A practical guide for communicating effectively with all people in all situations - St. John, Walter; Haskell, Ben (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2017)
The purpose of this book is to provide practicing and aspiring managers and students of management a practical and comprehensive reference source for communicating on the job with all people in all situations. This "how-to" book provides readers with the essential knowledge, attitudes, and skills to perform the communicating aspects of their routine and special duties. The information is presented in two volumes. Each topic is divided into "Things to Know" and "Things to Do."
Section 1. Topic 1. Sending effective messages -- Section 2. The four methods of communicating -- Topic 2. Tips for speaking effectively -- Topic 3. Delivering your speech -- Topic 4. Presiding over the question and answer period -- Topic 5. Overcoming speaker anxiety -- Topic 6. Introducing guest speakers properly -- Topic 7. Tips for listening effectively -- Topic 8. Using and interpreting body language -- Topic 9. Tips for writing effectively -- Topic 10. E-mail: do's and don'ts -- Topic 11. Editing techniques -- Topic 12. Proofreading methods -- Topic 13. Tips for reading effectively -- Section 3. Planning and conducting productive meetings -- Topic 14. Planning a meeting -- Topic 15. Conducting a meeting -- Topic 16. Contributing as a meeting participant -- Topic 17. Holding better one-on-one meetings -- Topic 18. Improving video and teleconferencing -- Section 4. Communicating skills for dealing with special situations -- Topic 19. Interviewing job applicants -- Topic 20. Orientating new employees -- Topic 21. Training people for the job -- Topic 22. Developing performance objectives, standards, and priorities of an organization -- Topic 23. Creating and agreeing on job descriptions -- Topic 24. Negotiating one-on-one -- Topic 25. Compromising to reach agreement -- Topic 26. Evaluating employee performance -- Topic 27. Coaching employees to improve performance -- Topic 28. Writing impressive news releases -- Topic 29. Communicating clearly with a diverse group of employees -- Topic 30. Communicating effectively with male and female employees -- Topic 31. Using sex fair language -- Section 5. Topic 32. Communicating attitudes and techniques for coping competently with difficult employees -- Index.
Includes index.
Title from PDF title page (viewed on February 2, 2017).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Communication in management; Reading Tips; Persuasive Communication; Managerial Communications; Management Skills; Managerial Performance; Listening Tips; Gender-Neutral; Diversity Communication; Conflict Resolution; Communication Skills; Communication Reference Guide for Managers; Communication Mistakes; Communication Guide for Managers; Communication Fundamentals; Communication Effectiveness for Managers; Communicating under Stress; Communicating Strategies; Communication; Communicating with Employees; Communicating in the Workplace; Communicating in a Crisis; Communicating for Managers; Communicating Effectively; Writing Tips; Workplace Communications; Workplace Situations; Speechmaking; Speaking Confidently; Electronic books